Integrating Papuan Local Cultural Content in English Narrative Reading Instruction: Strategies, Challenges, and Frameworks for Oral Tradition in EFL Contexts - Suhartawan, Vina Vania; Suryati, Nunung; Sujiatmoko, Ahmad Heki (VELES Voices of English Language Education Society, 2025)
English language teaching in Papua faces distinctive challenges due to its multilingual environment, geographical isolation, and reliance on undocumented oral traditions, yet limited research has examined how these realities shape culturally responsive pedagogy in EFL contexts. This study aimed to explore how English teachers at junior high, senior high, and university levels in Jayapura integrate Papuan local cultural content into narrative reading instruction, and to identify challenges in implementing such instruction when source materials are largely oral and undocumented. Guided by culturally responsive pedagogy and using a narrative inquiry design, three purposefully selected teachers participated in in-depth interviews, classroom observations, document analysis, and maintained reflective journals over three months. Data were analyzed thematically with cross-case comparison. Findings revealed six interrelated strategies, contextual substitution, community engagement, project-based cultural documentation, trilingual and bilingual vocabulary methods, and student-centered cultural knowledge exchange, through which teachers enhanced reading comprehension, cultural relevance, and student engagement. These strategies, however, were constrained by six persistent challenges: scarcity of documented materials, high individual material development burden, time constraints, cultural sensitivity and protocol requirements, curriculum rigidity, and professional isolation. The study offers an empirically grounded framework for integrating indigenous oral traditions into English reading instruction and highlights the need for institutional support, collaborative networks, and curriculum flexibility to preserve oral cultural heritage while strengthening students’ linguistic and cultural identities.